(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
The human body shape is the foundation of clothing structure design, it is important to analyze body shape accurately to satisfy people's demand for the fitness of clothing. With the improvement of people's requirements for the fit of clothing, the classification of body type is gradually refined. As a large group consumers of clothing products, middle-aged female body shapes are different from young and older women. This paper was based on the 3D human body measurement technology. 211 females' body data aged from 50 to 59 in central China were used as experiment samples. There are 26 body part sizes in total, including length, width and girth. Through the data analysis software SPSS, five types of body shape are obtained based on cluster analysis. Then the models of various types of middle-aged women were reconstructed, the specific characteristics of various types of body types were explained. Finally, the influence of body shape difference on the prototype version was studied by comparing the corresponding upper prototype of each body type. The research results of this paper can provide reference for the development of middle-aged women’s upper prototype.